The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1095/biolreprod.111.095224
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Reactive Oxygen Species and Antioxidants in Ovarian Toxicity1

Abstract: Proper functioning of the ovary is critical to maintain fertility and overall health, and ovarian function depends on the maintenance and normal development of ovarian follicles. This review presents evidence about the potential impact of oxidative stress on the well-being of primordial, growing and preovulatory follicles, as well as oocytes and early embryos, examining cell types and molecular targets. Limited data from genetically modified mouse models suggest that several antioxidant enzymes that protect ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
282
0
10

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(298 citation statements)
references
References 121 publications
6
282
0
10
Order By: Relevance
“…In most cells, including oocytes, ROS are removed by a series of antioxidant enzymes (Devine et al, 2012). RNA-seq and real-time PCR showed that in Kat8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cells, including oocytes, ROS are removed by a series of antioxidant enzymes (Devine et al, 2012). RNA-seq and real-time PCR showed that in Kat8…”
Section: Discussionmentioning
confidence: 99%
“…S5C). Continuous scavenging of ROS by antioxidant enzymes represents one cellular mechanism of defense against oxidative damage, which may compromise DNA integrity and cause oocyte apoptosis (Devine et al, 2012). Among the differently expressed genes after Kat8 deletion, the antioxidant genes peroxiredoxin 1 and 2 (Prdx1, Prdx2) and glutathione peroxidase 1 and 4 (Gpx1, Gpx4) were significantly downregulated in Kat8…”
Section: Fig 2 Kat8mentioning
confidence: 99%
“…Oocytes/PMF In human fetal ovary exposed to CTX, apoptosis was shown before in oocytes (PMF), than GCs [121] CTX metabolites induce H2AX, a marker of double strand DNA breaks predominantly in mouse oocytes (but also in GCs) cultured in vitro [122] GCs In the GCs of rat ovaries CTX damage to mitochondria induce the release of the cytocrome C into cytoplasm leading to cell apoptosis mediated by caspase family proteins. Damage in human GCs nuclei and follicular basement membranes [32,33,[122][123][124][125][126][127][128][129] Oxidative stress has been associated with CTX toxicity in GCs of mature follicles. CTX induces depletion in glutathione and rise in reactive oxygen species mediating apoptosis in GCs Stromal cells/vessels…”
Section: Mechanism(s) Of Ovarian Toxicity/features Of the Damage Refementioning
confidence: 99%
“…Treatment with cyclophosphamide results in a depletion of glutathione, a crucial cellular antioxidant, and a rise in reactive oxygen species that mediates apoptosis in granulosa cells (Tsai-Turton et al 2007, Devine et al 2012.…”
Section: Oxidative Stressmentioning
confidence: 99%